Strategies for new product diffusion: Whom and how to target? - Hu, Hai-hua; Lin, Jun; Qian, Yanjun; Sun, Jian (Journal of business research, 2018)
This paper examines the promotional strategies for new product diffusion by leveraging peer effects among consumers. Previous studies have offered conflicting recommendations on whom to target (e.g., influentials, susceptibles, or unsusceptibles) with respect to new product promotions. Utilizing agent-based modeling and simulation (ABMS), we show that each of the proposed consumer groups can be a promising target, depending on how they are targeted, according to target size and promotion intensity. The authors further recommend the optimal combination of whom and how to target under budget constraints. Specifically, where a budget is limited, the best approach is to target as many susceptibles as possible with a weak promotion. Targeting unsusceptibles with free products should be the first choice, where the budget is large. In other cases, the best approach is to target as many influentials as possible with a moderate promotion. •The study examines the promotional strategies for new product diffusion.•Three groups of target consumers are identified: influentials, susceptibles, and unsusceptibles.•Each of the proposed consumer groups can be a promising target, depending on target size and promotion intensity.•The influence of marketing budget on promotional strategies is explored.